AKSESIBILITAS MEDIA SOSIAL DAKWAH MAHASISWA KOMUNIKASI PENYIARAN ISLAM (KPI) IAIN PALU - Derwin Derwin; Suharto Suharto; Syamsuri Syamsuri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
This paper deals with accessibility of social media among Islamic Broadcasting Students of IAIN Palu. The question is how do students use social media to get information of Islamic preaching. The result showed that the students said that social media is highly beneficial for the development of preaching and knowledge need by the students. The reasons behind choosing social media are the easiness and quickness of access to it and time-saving. Meanwhile, social media to which students are enthusiastic include Facebook, WhatsApp, mailing list, blog, and so on. Facebook and Whatsapp are effective enough to establish relationship to others and get access to contents of Islamic preaching, while blog is used to explore information about Islam. In seeking information of Islam, Islamic Broadcasting (KPI) students used Google to carry out their task given by their lecturers and to improve their knowledge.